Ti-Girl Power: American Utopianism in the Queer Superhero Text - Matt Yockey (European Journal of American Studies)
This paper examines the ways in which artist-writer Jaime Hernandez engages with issues of national belonging in terms of ethnicity and gender in his 2012 superhero graphic novel God and Science: Return of the Ti-Girls. By presenting the adventures of a group of multi-racial female superheroes, Hernandez productively exploits the inherent social marginality of the superhero, conflating it with a comparable marginality of non-whites and women in American society. By doing so, he rearticulates that marginality as an actualization of the promise of pluralistic utopianism inherent in American society. As a Chicano and fan of Silver Age superhero comic books himself, Henandez also realizes this ethos for himself in the very creation of this work.